Kardiochirurgia dorosłych The role of cardiac surgery in treatment of acute coronary syndrome without ST elevation - Zembala, Marian; Kluba, Rafał; Gąsior, Mariusz; Przybylski, Roman; Kalarus, Zbigniew; Knapik, Piotr; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Implementation of a new definition and classification of acute coronary syndromes (ACS) has been bringing regular changes in treatment strategy. In this paper we present current experts guidelines for usage of surgical methods in NSTEACS treatment, clinical trials and registers review presenting significance of cardiac surgery and reflection of practical usage of guidelines. Moreover, we raise the problem of antiplatelet drugs usage before CABG depending on the procedure mode.